Essential psychology? Coleman, AM (ed) (1995) Longman Essential Psychology. London: Longman. 12 volumes. - Bradbury, Jill (PINS-Psychology in Society, 2026)
At last, a textbook with a different look! My shelves are crowded with complimentary copies of introductory texts, all American, each more glossy than the last and between their large, hard-covers, simply more of the same. The Longman Essential Psychology series appears enticingly different: twelve very short (approximately 100 pages) volumes in bright, soft-covers and inside, surprisingly, text - the written stuff rather than diagram after diagram and a plethora of full colour photographs. The separate binding of each volume allows for the purchase of just that "part• of the discipline which interests. This is a big plus in that very often a prescribed text contains much which is of no direct relevance to a course.